PLURALITAS ORIENTASI IDEOLOGI MUSLIM KLEPU SOOKO PONOROGO - Ulfah, Isnatin; Aminuddin, Luthfi Hadi (IAIN PONOROGO, 2024)
Klepu, a beautiful village at the eastern tip of Ponorogo Regency, has long been known as a model of harmonization between followers of different religions: Islam and Catholicism. However, if we take a closer and deeper look within the Muslim community itself, it turns out that there is quite severe ideological plurality. This research succeeded in capturing this plurality and the reasons behind it. Using a phenomenological approach, this research found that the process of ideological plurality within Klepu Muslims, who initially practiced Javanese Islam and then became diverse ideologies, occurred because of the process of cultural hybridization and diffusion brought by the Indonesian Islamic Da'wah Council (DDII) to the Klepu community. The presence of DDII, which was then followed by other similar preacher groups such as Muhammadiyah, was not value-free. They brought Puritan culture with a spirit of purifying Islam to Klepu. Then, the culture is selected by society so that attitudes of acceptance and rejection emerge to varying degrees. At this stage, the plurality of Klepu Muslim ideology occurred: Some accepted it ultimately, so they became Puritans. Some accept some elements of Puritan culture and reject some, then enter into a dialogue with their culture to produce new cultural entities and ideologies. However, some resist the presence of this new culture and continue to carry out the culture they have been practicing all this time.